The effect of templates on the morphological and optical properties of BaMgAl10O17:Eu2+ phosphors. (March 2019) - Jeet, Suninder; Pandey, O.P.
Abstract: Blue light emitting BaMgAl10 O17 :Eu 2+ phosphors were prepared by solution combustion synthesis method using urea as a fuel. Water-soluble templates, β-cyclodextrin and thioglycerol were used for the synthesis process. The main aim of the present work is to study the effect of these templates on morphology and optical properties of BaMgAl10 O17 :Eu 2+ phosphor. The inclusion of templates prevents agglomeration, hence improving crystallinity and photoluminescence emission intensity. β-cyclodextrin and thioglycerol modified the morphology of BaMgAl10 O17 :Eu 2+ phosphor by transforming its multifaceted plate-like to rod-like morphology. It is observed that the addition of β-cyclodextrin and thioglycerol in the synthesis of BaMgAl10 O17 :Eu 2+ phosphor not only increased the photoluminescence emission of BaMgAl10 O17 :Eu 2+ phosphor but also enhanced the thermal stability of the BaMgAl10 O17 :Eu 2+ phosphor. Hence the use of β-cyclodextrin and thioglycerol was beneficial in improving the crystallinity, photoluminescence characteristics and the thermal stability of BaMgAl10 O17 :Eu 2+ phosphor. Highlights: β-cyclodextrin and thioglycerol were used as templates in synthesis of BAM:Eu 2+ . Template addition improved crystallinity, morphology & photoluminescence emission. Phosphors obtained are thermally stable showing enhanced blue emission.